Phenology of cabbage stem flea beetle (Psylliodes chrysocephala L) in oilseed rape - Sivčev, Lazar I; Graora, Draga; Sivčev, Ivan; Tomić, Vladimir; Dudić, Boris (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2017)
The cabbage stem flea beetle (Psylliodes chrysocephala (L.) is an important pest of winter oilseed rape in Serbia. Beetles colonize oilseed rape in early October and are active in the field until first frost and wintertime. In autumn, adults can be seen laying eggs in the soil around plants. Larvae of P. chrysocephala developed intensively on leaf petioles in November, reaching their highest numbers at the end of the month. No infested plants were found in a conventional field, while 14.5% of all dissected leaf petioles were infested on an integrated field. On unprotected plants in an organic field, 76.0% of the plants were infested with larvae at the growth-stage BBCH 18-19, with 31.1% infested leaves on average. As a results, the number of plants was reduced by 51%, i.e. from 43.0/m2 recorded in the autumn to 22.0/m2 in the following spring. A new generation of P. chrysocephala beetles emerged from the soil in the first half of June and rapidly escaped the fields from almost dry plants. Our results showed that a part of the population stayed in aestivation and emerged in the following crop during the next season. On the following 5 March, 0.5 beetles/m2 were found in emergence cagesin the organic field, while 0.81beetles/m2 were found in the former trap crop.
Keywords: Cabbage stem flea beetle; Oilseed rape; Phenology